LOGISTICS SYSTEMS AND SUPPLY CHAINS IN THE CONTEXT OF GLOBALIZATION - Qo’chqorova Mukhlisakhon Ulug’bek qizi (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
In the era of globalization, logistics systems and supply chains play a crucial role in enhancing the efficiency, competitiveness, and resilience of businesses and economies. This article explores how globalization has transformed traditional logistics models into complex, internationally integrated networks. It highlights the key functions of logistics systems, the advantages and challenges of global supply chains, and the impact of digital technologies such as AI, IoT, and blockchain. The study concludes that strategic and innovative supply chain management is essential for navigating global risks and achieving sustainable development.